Quantifying the socio-economic benefits of music festivals: The case study of Phalaphala FM Royal Heritage festival - Mamotse Mokabe (Interdisciplinary Journal of Sociality Studies)
Understanding the socio-economic benefits of annual community festivals is vital for stakeholders like event planners and sponsors. This study, focused on Phalaphala FM Royal Heritage Festival, assumes festivals generate income for host communities and attract tourists. Using a dual approach (demand and supply perspectives), the study empirically evaluates these benefits, highlighting their impact on local economies and tourism. The aim is to assess and quantify the socio-economic advantages of music festivals for the host community. The research followed the quantitative method for both the demand and supply sides. The demand side collected data from sampled festival attendees; this was done face-to-face, while the supply collection of data from the SMMEs was done face-to-face and telephonically. The data was mainly analysed through descriptive analysis. The main findings revealed that retaining the earnings from the festival gains can be achieved by buying raw materials locally. Both the demand and supply sides depicted in the study show that the economic contribution of the festival involves the entire process of sourcing local produce from raw materials to finished products that may need to be done locally. However, the study established that buying locally might not be easy because some of the goods required are unavailable locally in the area. The festival greatly benefits both host communities and local businesses. The study recommends that there should be collaboration among local businesses to create packages (e.g., discounts for festivalgoers on food, accommodation, and transportation) to stimulate the local economy and to produce other raw materials locally.